The relationship between high‐sensitivity CRP and polyclonal Free Light Chains as markers of inflammation in chronic disease. (5th November 2013) - Burmeister, A.; Assi, L. K.; Ferro, C. J.; Hughes, R. G.; Barnett, A. H.; Bellary, S.; Cockwell, P.; Pratt, G.; Hutchison, C. A.
Summary Introduction Serum concentrations of polyclonal free light chains (FLC) represent the activity of the adaptive immune system. This study assessed the relationship between polyclonal FLC and the established marker of innate immunity, C‐reactive protein (CRP), in chronic and acute disease. Methods We utilized four cross‐sectional chronic disease patient cohorts: chronic kidney disease (CKD), diabetes, vasculitis and kidney transplantation; and a longitudinal intensive care case series to assess the kinetics of production in acute disease. Results There was a weak association between polyclonal FLC and high‐sensitivity CRP (hs‐CRP) in the study cohorts. A longitudinal assessment in acute disease showed a gradual increase in FLC concentrations over time, often when CRP levels were falling, demonstrating clear differences in the response kinetics of CRP and FLC in this setting. Conclusion Polyclonal FLC and hs‐CRP provide independent information as to inflammatory status. Prospective studies are now required to assess the utility of hs‐CRP and polyclonal FLC in combination for risk stratification in disease populations.